1991
DOI: 10.1080/03014469100001492
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of recall by middle-aged participants in a longitudinal study of their body size and indices of maturation earlier in life

Abstract: The validity of long-term recall and current assessments of height, weight, and fatness relative to peers was investigated among 91 middle-aged participants in a longitudinal growth study. The recollections of 50-year-old participants concerning perceived body size in comparison to peers during childhood (aged 5-7 years), adolescence (aged 10-18 years), and at ages 30, and 40 years were compared with physical measurements taken at these times. Correlations between perceived and actual body size at all ages fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
108
0
4

Year Published

1995
1995
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(117 citation statements)
references
References 29 publications
5
108
0
4
Order By: Relevance
“…Consistent with the results of other studies (23,24), a high proportion of subjects (62.1%) were able to recall accurately their ages at menarche. Similar to Koo and Rohan (23), we observed that the longer the interval between menarche and recall, the less accurate was the respondent's recall of age at menarche.…”
Section: Discussionsupporting
confidence: 81%
“…Consistent with the results of other studies (23,24), a high proportion of subjects (62.1%) were able to recall accurately their ages at menarche. Similar to Koo and Rohan (23), we observed that the longer the interval between menarche and recall, the less accurate was the respondent's recall of age at menarche.…”
Section: Discussionsupporting
confidence: 81%
“…A limitation of our study was that age at menarche was reported by recall many years later. However, other studies have shown high correlations (r=0.67 to 0.79) between age at menarche by recall during middle-age and the original childhood data [17,18]. Bias is unlikely and the observed association may therefore be slightly weakened by regression dilution.…”
Section: Discussionmentioning
confidence: 86%
“…(1,(5)(6)(7)(23)(24)(25)(26) This relationship has been mainly studied in women, partly because menarcheal age is a rather reliable and easily assessed measure of pubertal timing. (27)(28)(29) No similar self-reported measure is available in men. Age at PHV, used in the present study, is an objective assessment of pubertal timing that can be used in both genders.…”
Section: Discussionmentioning
confidence: 99%